2015
DOI: 10.1002/adsc.201500664
|View full text |Cite
|
Sign up to set email alerts
|

Carbocatalysed Oxidative CC Homocouplings of Benzo‐Fused Heterocycles

Abstract: Appropriate and fine-tuned treatments of amorphous carbon (AC) involving aqua regia or concentrated HNO 3 leadt oo xidised carbon materials (oAC) which are able to catalyse 2,2'-a nd 3,3'-homocouplings of various functionalised indoles with outstandinga ctivity.T his newly developed carbocatalysed C sp 2 À C sp 2 bondf ormation can be achieved under mild thermalc onditions.T he study on the scope of the reactionr evealed that the reaction can be extended to the homocoupling of other substrates of high syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 59 publications
1
39
0
1
Order By: Relevance
“…Recently, oxidized active carbon/oxygen, 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ)/MsOH, and NOBF 4 /oxygen systems were found to be applicable for the construction of 2,2′‐ or 3,3′‐coupled motifs starting from benzofused heterocycles such as indole, benzothiophene, or benzofuran.…”
Section: Intermolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, oxidized active carbon/oxygen, 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ)/MsOH, and NOBF 4 /oxygen systems were found to be applicable for the construction of 2,2′‐ or 3,3′‐coupled motifs starting from benzofused heterocycles such as indole, benzothiophene, or benzofuran.…”
Section: Intermolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
“…Recently,o xidized active carbon/oxygen, [38] 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)/MsOH, [39] and NOBF 4 /oxygen [40] systems were found to be applicable for the construction of 2,2'-o r3 ,3'-coupled motifs starting from benzofused heterocycles such as indole,b enzothiophene,o r benzofuran. Short-chain oligopyrroles constitute outstanding substrates for the formation of various pyrrolic macrocycles, which may vary significantly in their electronic properties and metal-binding properties.…”
Section: Oxidative Homocoupling Of Arenes and Heteroarenesmentioning
confidence: 99%
“…[10] We have previously reported that oxidized active carbon (oAC) can catalyze the CÀCb ond-forming ODH reactions of indoles and analogues in the presence of O 2 , [11] where experimental evidence points to the reaction proceeding via aradical mechanism involving quinoidic oxygen centers. [12,13] Based on this, we envisioned that carbocatalysis could be used as ah eterogeneous replacement for oxidative processes that are catalyzed or mediated by molecular quinones, [13,14] transition metals, [15] hypervalent iodines, [16] or nitrosoniums. [17] To that end, oxidized carbonn anotubes (oCNTs) would be the most suitable candidates as they offer significant advantages over oAC such as the high mechanicals trength, better stability towards oxidation by O 2 , [18] and fewerm icropores susceptible to catalystd eactivation.…”
mentioning
confidence: 99%
“…[36] Concerning the catalytic active site, we have previously observedacorrelation between the catalytic activity of the oAC and the amount of carbonyl groups in it. [12] In order to trace whether oCNTsb ehave similarly,t he catalystw as treated with phenylh ydrazine (PH) to selectivelyb lock the carbonyl/quinone groups of oCNTs. [37] When PH-oCNTsw ere used as catalyst, yields of 2a and 4a dropped to 0%.F urthermore, when oCNTsw ere replaced with tetracene, anthraquinone or 9,10phenanthrenequinone,y ields received were 0, 3, and 21 %o f 2a,r espectively (Figure 1, top).…”
mentioning
confidence: 99%
“…In den letzten Jahren wurden oxidierte Aktivkohle/Sauerstoff‐, 2,3‐Dichlor‐5,6‐dicyan‐1,4‐benzochinon (DDQ)/MsOH‐ und NOBF 4 /Sauerstoff‐Systeme als anwendbar für die Konstruktion 2,2′‐ oder 3,3′‐gekuppelter Motive aus benzanellierten Heterocyclen wie Indol, Benzothiophen oder Benzofuran identifiziert.…”
Section: Intermolekulare Oxidative Aromatische Kupplungunclassified